CONSUMER LIFESTYLE: A CASE ON USERS OF NATIONAL AND INTERNATIONAL BRAND LIPSTICK - Wulandari, Dewi; Agustini, Maria Yosephine Dwi Hayu (Universitas Brawijaya, Indonesia, 2019)
This research is aimed at understanding the lifestyle of users of national brand lipstick (Wardah) and international brand one (Revlon)using AIO variables that comprise of activity, interest, and opinion. Data was gathered from respectively 30 lipstick users of Wardah and 30 of Revlon who reside in Semarang using questionnaire. Description analysis was to describe the lifestyle of both samples and then was analyzed using an independent t test for two unrelated samples to know if they differ in their lifestyle. The results show that there are differences of lifestyle between two groups of the sample in which the Wardah users are more likely dominant in the variable of interest while the Revlon users are more likely dominant in the variable of activity and opinion. Segmentation and targeting strategy according to consumers'lifestyle are thus important for succeeding the company.